Lesbian Performativity and Heteronormativy in The Novel Lesbian Laki-Laki by Deojha: Judith Butler - Agung Wijaksono; Nurhadi Nurhadi (Syntax Corporation Indonesia, 2022)
Lesbians are a testament to sexual diversity in society, but in reality, the existence of minorities is still faced with the dilemma of norms in society. The condition occurs since people still acknowledge heteronormality or only consider heterosexual orientation deemed normal. This study was designed to describe lesbian performativity and heteronormativity in the novel Lesbian Laki-Laki (Male Lesbian) by Deojha's using the Judith Butler's theory of Queer. This study used a descriptive qualitative research method. The results showed that gender and sexual identity discourse are constructed by language and body markers. The heterosexual discourse of acceptable gender identity only involves masculinity and femininity, then sexually divided into two parts, called male and female. The analysis also proved that although the novel voiced lesbian order but still in the norms of heteronormativity